THE EFFECT OF TAXATION RATIONAL ATTITUDE, RELIGIUSITY, AND ETHICS ON TAXPAYER COMPLIANCE (JOURNAL OF ACCOUNTING, ENTREPRENEURSHIP AND FINANCIAL TECHNOLOGY (JAEF), 2022)
The role of taxes is very important in securing the State Revenue and Expenditure Budget (APBN), therefore tax revenues are expected to grow from time to time. One of the efforts of the Directorate General of Taxes in increasing tax revenues, one of which is to use the Self-assessment System, which is a system that requires taxpayers to calculate, pay, and selfreport the tax payable, so that the determination of the amount of tax is entrusted to the taxpayers themselves. However, in practice the Self-assessment System is difficult to run as expected and is often misused. This makes researchers interested in studying the factors that influence taxpayer compliance using a behavioral approach (behavioral cooperation). The sample used is individual taxpayers registered in all KPPs in the city of Surabaya. This study uses a questionnaire distributed through Google Form. The data collection method used is primary data collection. The data analysis used in this research is multiple regression analysis. This study shows the results that Rational Attitudes, Religiosity, and Tax Ethics have a positive influence on taxpayer compliance. Keywords: rational attitude, religiosity, tax ethics, taxpayer compliance.